PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR FISIKA KELAS X SMA - Despita Despita (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
This classroom action research was conducted to improve the process and achievement of students in learning Physical subject throug implementation of learning model Think Pair Share. This research was conducted in 2022, it iwas implemented in Phyisical subject at class X IPA 2 SMAN 12 Bungo involving 30 students as the research objects. The research was conducted using students’ observation sheet, teacher’s observation sheet, and test. Based on the observation, it could be seen that the students join the class more actively. It was crealy seen that the students’ motivation increased from one cycle to another cycle. The observation sheet showeed that the first cycle was 68,4%, and it was increased in cycle 2, 86,3%. Not only that, the students’ achievements were increased as the process. It was seen from the first cycle test, 56,6% of students pass the standard, it was increased 20 % from the pre test results. And then, it was increased higer in the second cycle, 76,6%.